Aggregated impact of coordinated commercial-scale battery energy storage systems on network peak demand, and financial outcomes. (July 2021) - Zhou, Hou Sheng; Passey, Rob; Bruce, Anna; Sproul, Alistair B.
Abstract: The penetration of distributed battery energy storage systems in electricity grids globally is forecast to grow rapidly over the next 10 years. These systems can provide benefits for the customers that install them, but also introduce new opportunities and challenges for distribution network operators. This paper presents an algorithm that optimises the sizing and operation of a cluster of battery energy storage systems in commercial buildings. It aims to either optimise the battery energy storage system independently to maximise the financial benefits for each building or coordinate them to maximise the value of reducing demand peaks for both the customer and the local zone substation. To achieve the latter, the algorithm assumes a certain percentage of the network deferment value associated with reducing the peak demand for the zone substation is passed through to customers. Scenario analysis show that the peak demand reduction and financial outcomes for both the building owners and the network result from a complex interaction between the customer and network load profiles, the tariff structure, the size and cost of the BESS, and the percentage of the network deferment value that is passed through. Highlights: Optimised battery size and operation for a cluster of commercial building. Optimisation model included a deferment value (NDV) for reducing substation peaks. Results showed that the NDV was effective in encouraging larger battery sizes. Best outcome for network operators is when half of the NDV is shared with customers. Not including the NDV can still result in beneficial outcomes for customers.